RDNA-13. VALIDATION OF BEHAVIORAL ANALYSIS ACROSS AGE IN A MOUSE MODEL FOR FUTURE INVESTIGATION OF RADIATION-INDUCED HYPERSOMNOLENCE (RIH) IN PRIMARY BRAIN TUMOR (PBT) PATIENTS. (5th November 2018) - Figiel, Caitlin; Shuboni-Mulligan, Dorela; Armstrong, Terri; Smart, DeeDee
Abstract: BACKGROUND: Cranial radiation is part of standard PBT treatment with patient age recognized to impact response and toxicity. RIH is one of the most common toxicities. We have reported an association between circadian gene variants and RIH susceptibility. No rodent model for RIH has been validated. The purpose of this study is to evaluate the impact of age on activity and circadian behavior to inform our novel mouse model of RIH. METHODS: Ethovision XT Software and Phenotyper cages wereused to continually video animal behavior and generate general activity data. Male young (6wk, n=3) or old (18mo, n=3) C57BL/6 mice were individually housed. Mice were monitored for 10 days under 12:12hr light:dark conditions. The data was examined for activity and circadian parameters. RESULTS: Older mice had lower total activity levels (-36%) than younger controls, with greatly decreased levels during the active period (-49%) but increased levels during the sleep period (49%). Actograms of general activity binned in 10 min intervals demonstrated a dramatic impact of age on circadian rhythms. Older mice displayed a dampened amplitude of activity rhythms (-36%; t= 4.1, p< 0.01) and higher phase angle of entrainment (40.3 ± 25.8min) compared to younger mice (-1.11 ± 0min). Earlier activity onset in older animals increased the total activity period (alpha) by 7% (t=2.9, p <0.05). Both general activity and circadian data collected with Ethovision XT provided clear validation of the technique. CONCLUSIONS: Activity, sleep and circadian rhythms are impacted by irradiation in patients. A good behavioral model to observe these changes has not yet been developed in rodents. Here we demonstrate a reliable system to collect/ analyze both activity and circadian parameters. Our study demonstrates a clear difference in all parameters at age extremes for control animals, a factor that warrants inclusion in our RIH model designed to recapitulate the human experience.